Optimized adsorption onto biosolids‐based activated carbon for tartrazine removal from wastewater. (25th February 2019) - Madeira, Carla Suély P.; Zavarize, Danilo G.; Vieira, Gláucia Eliza G.
Abstract: This study investigates optimized tartrazine uptake by activated carbon prepared from biosolids (BBAC). Different tartrazine concentrations (10–20 mg/L), adsorbent dosages (1.0–2.0 g), pH (2.0–4.0), and contact times (60–120 min) were tested. These independent variables formed a 2 4 full factorial experiment arranged as central composite rotative design (CCRD). Response surface methodology (RSM) analyzed the responses of 50 experimental runs. Tartrazine removal efficiency fluctuated between 76.2% and 99.9%. The experimental data were best fitted by a quadratic model ( R 2  > 0.95, p  >   0.0001). All variables exerted statistically significant ( p  <   0.05) effects on the tartrazine uptake (initial concentration, p  =   0.0011; BBAC dosage, p  =   0.0004; pH, p  <   0.0001; contact time, p  <   0.0001). Optimized tartrazine uptake efficiency of 97.4% can happen when variables mutually correlate at 10.1 mg/L of tartrazine concentration, 1.07 g of adsorbent dosage, 2.13 of pH, and 116.9 min of contact time. Practitioner points: Production of biosolids‐based activated carbon (BBAC) is presented. Adsorptive affinity to tartrazine in aqueous solution was experimented. Experimental conditions optimized by Response Surface Methodology.